THE EXISTENCE OF MAK YONG MASK PERFORMANCE AS MANTANG ISLAND TOURISM ATTRACTION - Ntan Era Komala, Arbi; Bava, Saliha (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This article aims to describe and reveal the existence of Mak Yong Mask Performing Arts as a Tourist Attraction on Mantang Island. Mak Yong mask is a traditional performing art of the Malay community which consists of a combination of ritual elements, performing arts, dance, music creation and singing. This show has been recognized by UNESCO (United Nations Educational, Scientific and Cultural Organization) as an intangible cultural heritage belonging to a group of three countries, namely Malaysia, Thailand, and Indonesia. Mak Yong's mask on Mantang Island itself has a characteristic that is the use of masks as its property. Qualitative research methods are carried out using interview, observation, and literature studies. The Sociological Dance approach is used to examine the social role of society in the development of the performing arts itself. The results of the discussion in this study indicate the development of the performing arts of Makyong masks on the island of Mantang as an indicator of the existence of performing arts, one of the important aspects and has a relationship with government efforts in developing the tourism sector. The function of performing arts as a tourist attraction is packaged in the form of cultural tourism.